Entrepreneurship environment in New Zealand : the Atlantis group. - Chang, Ee Chia. (2008)
A study of critical factors that contribute to entrepreneurial success of a New Zealand firm - The Atlantis Group (TAG). 1. Critical conditions, which could possibly influence the start-up of the company. 2. Explore the effect of Corporate Entrepreneurship (CE) upon TAG’s subsequent growth and development.